Flexible self-supporting graphene electrode material and preparation and application method thereof

By oxidizing and peeling the carbon paper by using a low-temperature strong oxidant-sulfuric acid-nitric acid system in the preparation of graphene CDI electrode materials, and improving the conductivity through steam thermal reduction of hydrazine hydrate, the problem of conductive agents and binders affecting the electroactive sites and transport properties in the prior art is solved, and graphene electrode materials with high specific surface area, good conductivity and flexibility characteristics are achieved, which significantly improves the electrochemical performance and salt adsorption ability.

CN119750564APending Publication Date: 2025-04-04CHENGDU TECH UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510033707.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the existing preparation methods for graphene CDI electrode materials, the introduced conductive agents and binders will affect the electroactive sites and electron/ion transport performance of the active material, and the material is not flexible and difficult to adapt to different operating environments.

Method used

A flexible self-supporting graphene electrode material is prepared by integrating a fluid, binder, conductive agent and adsorption material. The carbon paper is oxidized and peeled off by a low-temperature strong oxidant-sulfuric acid-nitric acid system to form a graphene sheet layer and a mesh structure, and the conductivity is improved by steam thermal reduction of hydrazine hydrate.

Benefits of technology

It realizes graphene electrode materials with high specific surface area, good conductivity and flexibility without the need for additional materials such as conductive agents and binders, which significantly improves electrochemical performance and salt adsorption ability, and has good stability and flexibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750564A_ABST
    Figure CN119750564A_ABST
Patent Text Reader

Abstract

The invention discloses a flexible self-supporting graphene electrode material and a preparation and application method thereof. The preparation method comprises the following steps: obtaining a low-temperature strong oxidant-concentrated sulfuric acid-concentrated nitric acid system, carrying out normal-temperature oxidation stripping on carbon paper by using the system, carrying out hydrogen peroxide treatment, cleaning and freeze drying on the stripped carbon paper, and then carrying out hydrazine hydrate steam thermal reduction, cleaning and freeze drying to obtain the flexible self-supporting graphene electrode material. The material has a graphene sheet layer and carbon fiber interwoven structure, the surface of the material contains a large number of oxygen-containing groups, and the material has a relatively high specific surface area, good conductivity, extremely high hydrophilicity and excellent flexibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of graphene materials, and in particular to a flexible self-supporting graphene material that can be used as an electrode for capacitor deionization. Background Art

[0002] Capacitive deionization (CDI), as a new brackish water desalination technology, has attracted extensive attention due to its significant advantages such as high efficiency, energy saving, environmental protection, simple equipment and low cost compared with traditional desalination technologies (such as reverse osmosis, multi-effect distillation, electrodialysis, etc.). Among the many electrode materials for CDI, graphene electrode has a high theoretical specific surface area (2600 m 2 / g), excellent electrical conductivity (7200 S / m) and good mechanical strength and so on, and have been widely studied.

[0003] At present, the most widely used method for preparing graphene CDI electrodes is to prepare a slurry mixture of graphene-based active materials, binders and conductive agents in a certain proportion, and evenly coat it on the surface of conductive substrates such as carbon paper, carbon cloth and other conductive substrates, that is, the traditional slurry coating method. However, the conductive agent and binder introduced by this preparation method will interact with the active material and reduce the electroactive sites of the active material, affecting the CDI performance. Among them, the introduced binder will also form an isolation layer to affect the transmission performance of electrons / ions and increase energy loss. At the same time, the electrode prepared by the coating method also has the problem of weak adhesion between the active material and the conductive substrate and easy to fall off, which has a very obvious impact on the performance of CDI, especially the long-term stability. In addition, the graphene material obtained by the above preparation method is not flexible and difficult to adapt to the requirements of different deionization operating environments. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a new flexible self-supporting graphene electrode material that integrates a current collector, a binder, a conductive agent and an adsorbent material, as well as a preparation method and an application method in a micro-capacitor deionization device. The electrode material is a flexible material with a self-supporting function and can be directly used as an electrode without the introduction of other materials such as a conductive agent, a binder and a conductive agent base.

[0005] The technical solution of the present invention is as follows: A method for preparing a flexible self-supporting graphene electrode material, comprising: (1) obtaining a mixed solution of a solid strong oxidant and concentrated sulfuric acid at a constant temperature of 0° C., i.e., a first mixed solution; (2) adding concentrated nitric acid to the first mixed solution and mixing them evenly to obtain a second mixed solution; (3) soaking the carbon paper in the second mixed solution at room temperature for 24-48 hours, and baking the soaked carbon paper at 30-50° C. for 6-10 hours to obtain peeled carbon paper; (4) washing the peeled carbon paper and adding hydrogen peroxide to treat it until the unreacted strong oxidant is completely removed to obtain treated carbon paper; (5) washing the treated carbon paper with acid, water and anhydrous ethanol in sequence, and then performing a first freeze-drying to obtain a three-dimensional graphene oxide material; (6) adding the three-dimensional graphene oxide material to distilled water containing hydrazine hydrate, and reducing it at 75-90° C. for 12-36 hours to obtain a reduced electrode material; (7) washing the reduced electrode material with water and anhydrous ethanol, and then performing a second freeze-drying to obtain a flexible self-supporting graphene electrode material; Wherein, the volume ratio of the concentrated sulfuric acid to the concentrated nitric acid is 3-5:1.

[0006] The raw material carbon paper used in the above preparation method of the present invention is composed of a large amount of graphite powder and carbon fiber. The room-temperature oxidation stripping of the carbon paper by a low-temperature strong oxidant-sulfuric acid-nitric acid system formed by a strong oxidant, concentrated sulfuric acid and concentrated nitric acid at low temperature can increase the surface defects of the carbon paper, which is beneficial to improving the electrode performance. At the same time, it can introduce a large number of oxygen-containing groups to its surface, convert the carbon paper from hydrophobic to strongly hydrophilic, increase its wettability in the electrolyte solution, and make it in situ stripped to form obvious graphene sheets and network structures, greatly improving the specific surface area of ​​the material. In addition, the graphene produced by its in-situ stripping and the carbon fibers of the carbon paper itself produce an interwoven structure, which makes it have significant flexibility characteristics. The conductivity can be further improved by thermal reduction with hydrazine hydrate vapor and the ion / electron transmission performance can be improved.

[0007] The above preparation method of the present invention can be carried out at a relatively low temperature throughout the entire process, without the need for electrochemical reaction, and can effectively reduce energy and cost consumption.

[0008] According to some preferred embodiments of the present invention, the solid strong oxidant is selected from one or more of potassium permanganate, potassium ferrate and potassium perchlorate.

[0009] According to some preferred embodiments of the present invention, the solid-to-liquid ratio of the first mixed solution is 0.1-0.3 g / ml.

[0010] According to some preferred embodiments of the present invention, the thickness of the carbon paper is 0.01-0.5 mm.

[0011] According to some preferred embodiments of the present invention, the concentration of the hydrogen peroxide is 25-35wt%.

[0012] According to some preferred embodiments of the present invention, the temperature of the first freeze-drying is -50°C to -35°C, and the temperature of the second freeze-drying is -50°C to -35°C.

[0013] According to some preferred embodiments of the present invention, the pickling uses hydrochloric acid with a concentration of 1-1.5 mol / L.

[0014] The present invention further provides a flexible self-supporting graphene electrode material prepared according to the above preparation method.

[0015] The flexible self-supporting graphene electrode material is a flexible porous structure with a typical graphene sheet structure and a larger interlayer spacing, which greatly improves the specific surface area and conductivity of the material. At the same time, it retains the interweaving between the carbon fiber rods and the graphene structure, making the material have excellent flexibility. It can withstand large pressure deformation under artificial bending and folding, and can restore the original morphology without destroying the overall structure. At the same time, it is light in weight, with an overall volume density of about 0.28 g / cm 3 Much lower than the density of carbon paper itself (2.34 g / cm 3 ).

[0016] This flexible self-supporting graphene electrode material has a high specific surface area, good conductivity, strong hydrophilicity and excellent flexibility. It can be directly used as an electrode without the addition of additional binders, conductive agents and current collectors, and can be widely used in capacitor deionization, dye and heavy metal adsorbents, catalyst active ingredient carriers, etc.

[0017] The present invention further provides the application of the above-mentioned flexible self-supporting graphene electrode material in a capacitor deionization electrode.

[0018] The flexible self-supporting graphene electrode material obtained by the present invention can be directly used as an electrode without adding a current collector, a binder, a conductive agent, etc. It has excellent electrochemical properties, and the surface capacitance is as high as 1.43F / cm at a scanning rate of 10 mV / s. 2 ; It has excellent salt adsorption capacity. When the initial concentration of NaCl solution is 50 mg / L and 500 mg / L, its surface adsorption capacity is as high as 322.21 and 581.15 mg / m 2 ; At the same time, it has excellent flexibility and stability, and can still maintain a good shape after curling and folding more than 500 times, and there is no obvious attenuation of salt adsorption. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1The SEM comparison images of the carbon paper and the flexible self-supporting graphene electrode material in Example 1, wherein (a) and (b) are SEM images of the carbon paper, and (c) and (d) are SEM images of the flexible self-supporting graphene electrode material; Figure 2 TEM comparison images of the carbon paper and the flexible self-supporting graphene electrode material in Example 1, wherein (a) is a TEM image of the carbon paper, and (b) is a TEM image of the flexible self-supporting graphene electrode material; Figure 3 XRD comparison spectra of carbon paper and flexible self-supporting graphene electrode material in Example 1; Figure 4 RM comparison spectra of carbon paper and flexible self-supporting graphene electrode materials in Example 1; Figure 5 This is a comparative XPS spectrum of the carbon paper and the flexible self-supporting graphene electrode material in Example 1; Figure 6 This is the C 1s spectrum of the flexible self-supporting graphene electrode material in Example 1; Figure 7 A comparison of N2 adsorption-desorption isotherms of carbon paper and flexible self-supporting graphene electrode materials in Example 1; Figure 8 This is a comparison chart of the impedance test results of the carbon paper and the flexible self-supporting graphene electrode material in Example 1; Fig. 9 This is a comparison diagram of brackish water desalination curves of the carbon paper and the flexible self-supporting graphene electrode material in Example 1; Fig.10 The CDI Ragone diagram of the carbon paper and the flexible self-supporting graphene electrode material in Example 1 at a voltage of 1.2 V and a 50 mg / L NaCl solution; Fig.11 Cyclic voltammetry performance test of the flexible self-supporting graphene electrode material and the coated electrode in Example 1 in 1M NaCl solution at a scan rate of 10 mV / s; Fig.12 is the specific capacitance of the flexible self-supporting graphene electrode material and the coated electrode at different scan rates in Example 1; Fig.13 The graph is a comparison of brackish water desalination curves of the flexible self-supporting graphene electrode material and the coated electrode in Example 1; Fig.14 The CDI Ragone diagram of the flexible self-supporting graphene electrode material and the coated electrode in Example 1 at a voltage of 1.2 V and a 50 mg / L NaCl solution; Fig.15 Schematic diagram of the flexibility investigation of the flexible self-supporting graphene electrode material in Example 1; Fig.16 This is a test chart showing the effect of the number of times the flexible self-supporting graphene electrode material is curled on the brackish water desalination performance in Example 1. DETAILED DESCRIPTION

[0020] The technical scheme of the present invention will be further described below in conjunction with the embodiments and drawings of the present invention. The embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0021] Example 1 The flexible self-supporting graphene electrode material was prepared by the following steps: (1) Slowly add 11 g KMnO4 into 90 mL concentrated H2SO4 in an ice water bath and stir until completely dissolved to obtain a first mixed solution. After the first mixed solution is cooled, add 10 mL concentrated HNO3 and continue stirring to obtain a second mixed solution. (2) Two pieces of carbon paper with a length and width of 8 cm and 4 cm respectively and a total mass of about 1.1 g were placed flat in a petri dish, and the obtained second mixed liquid was slowly poured into the petri dish until the carbon paper was completely immersed, and then the petri dish was sealed with plastic wrap for room temperature pre-oxidation; after pre-oxidation for 24 h, the sealed petri dish was transferred to a 40 °C oven and baked for 6 h for deep oxidation peeling to obtain peeled carbon paper; (3) Add 200 mL of deionized water to the culture dish containing the peeled carbon paper for dilution, and then add 30 wt % H2O2 dropwise until no bubbles are generated after cooling, remove the unreacted KMnO4, and obtain the treated carbon paper; (4) washing the treated carbon paper with 1 mol / L HCl, deionized water and anhydrous ethanol in sequence to remove impurities, and then freeze-drying the carbon paper at a freezing temperature of -30°C to obtain a three-dimensional graphene oxide material; (5) The three-dimensional graphene oxide material was placed in distilled water containing 2 mL of hydrazine hydrate and hydrothermally reduced at 80 °C for 10 h to obtain a reduced electrode material. The reduced electrode material was washed with deionized water and anhydrous ethanol and freeze-dried again at a freezing temperature of -30 °C to obtain a flexible self-supporting graphene electrode material.

[0022] After testing, the mass of the flexible self-supporting graphene electrode material obtained in this embodiment is 478.3±40.3 mg.

[0023] The obtained flexible self-supporting graphene electrode material was characterized microscopically and compared with the microstructure of the original carbon paper. Figure 1The SEM contrast images and attached Figure 2 The TEM contrast images shown are from the attached Figure 1 It can be seen that the original carbon paper is made by pressing carbon fiber and graphite powder. The graphene material after oxidation etching and thermal reduction retains the original carbon fiber structure, and the carbon powder on its surface shows obvious signs of oxidation etching. Further, it can be clearly seen from the SEM under a high-power microscope that compared with the original carbon paper graphite structure, the flexible self-supporting graphene electrode material has a typical graphene sheet structure, which greatly improves the specific surface area and conductivity of the material. In addition, the carbon fiber rods retained in the material are intertwined with the formed graphene structure, giving the synthesized electrode material excellent flexibility. From the attached Figure 2 It can be seen from TEM that compared with the original carbon paper, the flexible self-supporting graphene electrode material has a typical graphene sheet structure and a larger interlayer spacing, which is conducive to the diffusion and transmission of ions.

[0024] Furthermore, the flexible self-supporting graphene electrode material and the raw carbon paper were characterized by XRD, RM and XPS, and the results are shown in the attached figures. Figure 3 and 4 shown. Figure 3 The XRD spectrum of the original carbon paper shows two obvious diffraction peaks at (002) and (004), which are typical graphite structures, while the XRD spectrum of the flexible self-supporting graphene electrode material only shows a diffraction peak at (002), which means that the graphite powder is effectively exfoliated and the resulting material is an amorphous structure. Figure 4 In the RM spectrum, the ratio of D-band to G-band is obviously higher in the flexible self-supporting graphene electrode material than in the original carbon paper, which further confirms that the original carbon paper is effectively oxidized and etched in the mixed solution of KMnO4-H2SO4-HNO3 to form an amorphous structure of graphene.

[0025] Among them, the XPS spectra of the original carbon paper and the flexible self-supporting graphene electrode material are shown in the attached figure. Figure 5 As shown, it can be seen that the carbon content on the surface of the flexible self-supporting graphene electrode material has decreased significantly, while the oxygen content has increased significantly, indicating that the carbon paper has been effectively peeled off. At the same time, the HNO3-assisted oxidation etching introduced some nitrogen, which helped to improve the wettability and conductivity of the material.

[0026] The N2 adsorption-desorption isotherms of the original carbon paper and the flexible self-supporting graphene electrode materials were tested, and the results are shown in the attached figure. Figure 6As shown in the figure, it can be seen that the flexible self-supporting graphene electrode material has a higher nitrogen adsorption capacity, while the original carbon paper has a nitrogen adsorption capacity of almost 0, which indicates that the carbon paper is effectively chemically oxidized and exfoliated under the conditions of KMnO4-H2SO4-HNO3 to form a larger active area. Further calculations show that the specific surface area and pore size of the flexible self-supporting graphene electrode are 321.3 m 2 / g, 1.8 nm, which is significantly higher than the specific surface area of ​​the original carbon paper (10.2 m 2 / g) and pore size (0.4 nm).

[0027] The cyclic voltammetry performance of the original carbon paper and the flexible self-supporting graphene electrode materials was tested in 1 mol / L NaCl solution at a scan rate of 10 mV / s. Figure 7 As shown. It can be seen that at the same scan rate, the area enclosed by the CV curve formed by the flexible self-supporting graphene electrode material is larger, while the area enclosed by the CV curve of the original carbon paper is almost negligible, which indicates that the flexible self-supporting graphene electrode material has a larger specific capacitance and ion transport performance. The specific capacitance of the flexible self-supporting graphene electrode material is calculated to be 1.6 F / cm 2 , significantly higher than the original carbon paper (0.015 F / cm 2 ).

[0028] Further, as attached Figure 8 As shown, it can be clearly seen from the electrochemical AC impedance test spectrum that the flexible self-supporting graphene electrode material has a lower resistance, indicating that it has a higher ion / electron transport performance. The above electrochemical test results further reveal that it is an effective means to prepare a flexible self-supporting graphene electrode by oxidative etching of carbon paper with a KMnO4-H2SO4-HNO3 mixed solution.

[0029] The capacitive deionization performance of the original carbon paper and the prepared flexible self-supporting graphene electrode material was tested for brackish water desalination, that is, the adsorption performance was tested for 60 min at an applied voltage of 1.2 V and a NaCl solution concentration of 50 mg / L in the feed solution. The results are shown in the attached figure. Fig. 9 As shown in the figure, it can be seen that the NaCl concentration decreases over time, indicating that Na + and Cl - The NaCl concentration of the original carbon paper as an electrode hardly changed, indicating that the original carbon paper itself has no adsorption capacity. Fig.10 It can be seen from the CDI Ragone diagram shown that the flexible self-supporting graphene electrode material has a higher NaCl adsorption amount and removal rate.

[0030] Furthermore, the electrochemical properties and capacitive deionization performance of the flexible self-supporting graphene electrode material obtained in Example 1 were compared with those of the graphene electrode obtained by the coating method, i.e., the coated electrode, wherein the coated electrode was obtained by the following steps: (1) Grind 478.3±40.3 mg of graphene, an electrode material, into fine powder, mix it with polytetrafluoroethylene (PTFE) as a binder and carbon black (carbon black) as a conductive agent in a mass ratio of 8:1:1, and add a small amount of N-methylpyrrolidone as a solvent and continue grinding to obtain an electrode slurry; (2) The electrode slurry was evenly coated on two pieces of carbon paper with a size of 8 cm × 4 cm and dried in an oven at 70 °C to obtain two graphene electrodes, namely, graphene double electrodes.

[0031] The graphene double electrode and the flexible self-supporting graphene electrode material were tested for cyclic voltammetry in 1 M NaCl solution at a scan rate of 10 mV / s. The results are shown in the attached figure. Fig.11 and 12 shown.

[0032] from Fig.11 It can be seen that the CV curve of the flexible self-supporting graphene electrode material has a larger area, indicating that it has a higher specific capacitance than the coated electrode; Fig.12 The rate performance in the scan rate range of 1-100 mV / s also shows that the flexible self-supporting graphene electrode material has better ion storage performance.

[0033] The graphene double electrode and the flexible self-supporting graphene electrode material were tested for capacitive deionization performance at 1.2 V voltage and 50 mg / L NaCl solution. The results are shown in the attached figure. Fig.13 and 14 As shown. Fig.13 It can be seen that the NaCl concentration change curve of the coated electrode is significantly higher than that of the flexible self-supporting graphene electrode material, indicating that the flexible self-supporting graphene electrode material has better NaCl adsorption performance; Fig.14 It shows that the flexible self-supporting graphene electrode has higher NaCl enrichment capacity and adsorption rate.

[0034] Furthermore, the flexible self-supporting graphene electrode material obtained in Example 1 was repeatedly bent and folded 500 times to examine its flexibility. The results are shown in the attached figure. Fig.15 As shown, it can be seen that the material can still maintain its original shape well after 500 bending and folding, indicating that it has good flexibility.

[0035] Furthermore, the stability of the flexible self-supporting graphene electrode material after multiple curling treatments was investigated in a 1.2 V voltage and 50 mg / L NaCl solution. The results are shown in the attached figure. Fig.16 It can be seen that after 250 and 500 repeated bending and folding, the desalination performance of the material did not decay significantly, indicating that the material performance is stable.

[0036] All other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

Claims

1. A method for preparing a flexible self-supporting graphene electrode material, characterized in that: It includes: (1) obtaining a mixed solution of a solid strong oxidant and concentrated sulfuric acid at a constant temperature of 0° C., i.e., a first mixed solution; (2) adding concentrated nitric acid to the first mixed solution and mixing them evenly to obtain a second mixed solution; (3) soaking the carbon paper in the second mixed solution at room temperature for 24-48 hours, and baking the soaked carbon paper at 30-50° C. for 6-10 hours to obtain peeled carbon paper; (4) washing the peeled carbon paper and adding hydrogen peroxide to treat it until the unreacted strong oxidant is completely removed to obtain treated carbon paper; (5) washing the treated carbon paper with acid, water and anhydrous ethanol in sequence, and then performing a first freeze-drying to obtain a three-dimensional graphene oxide material; (6) adding the three-dimensional graphene oxide material to distilled water containing hydrazine hydrate, and reducing it at 75-90° C. for 12-36 hours to obtain a reduced electrode material; (7) washing the reduced electrode material with water and anhydrous ethanol, and then performing a second freeze-drying to obtain a flexible self-supporting graphene electrode material; Wherein, the volume ratio of the concentrated sulfuric acid to the concentrated nitric acid is 3-5:

1.

2. The preparation method according to claim 1, characterized in that: The solid strong oxidant is selected from one or more of potassium permanganate, potassium ferrate and potassium perchlorate.

3. The preparation method according to claim 2, characterized in that: The solid-to-liquid ratio of the first mixed solution is 0.1-0.3 g / ml.

4. The preparation method according to claim 1, characterized in that: The thickness of the carbon paper is 0.01-0.5 mm.

5. The preparation method according to claim 1, characterized in that: The concentration of the hydrogen peroxide is 25-35wt%.

6. The preparation method according to claim 1, characterized in that: in, The temperature of the first freeze-drying is -50°C to -35°C, and the temperature of the second freeze-drying is -50°C to -35°C.

7. The preparation method according to claim 1, characterized in that: The pickling uses hydrochloric acid with a concentration of 1-1.5 mol / L.

8. A flexible self-supporting graphene electrode material prepared according to the preparation method described in any one of claims 1 to 7.

9. Use of the flexible self-supporting graphene electrode material according to claim 8 in a capacitor deionization electrode.

Citation Information

Patent Citations

  • Graphene paper and preparation method and application thereof

    CN103700513A

  • Method for large-area preparation of graphene based carbon paper and graphene based carbon paper prepared thereby

    CN104261387A

  • Method for preparing lithium ion battery anode / cathode material from reduced graphene oxide

    CN104617300A

  • Preparation method and electrochemical performance test method of anode material graphene

    CN106853965A

  • Low-temperature thermal forming method for three-dimensional graphene material

    CN107140626A